Mood, anxiety and psychotic phenomena measure a common psychopathological factor. Issue 7 (14th November 2014) - Stochl, J.; Khandaker, G. M.; Lewis, G.; Perez, J.; Goodyer, I. M.; Zammit, S.; Sullivan, S.; Croudace, T. J.; Jones, P. B.
Abstract : Background: Psychotic phenomena are common in the general population but are excluded from diagnostic criteria for mild to moderate depression and anxiety despite their co-occurrence and shared risk factors. We used item response theory modelling to examine whether the co-occurrence of depressive, anxiety and psychotic phenomena is best explained by: (1) a single underlying factor; (2) two separate, uncorrelated factors; (3) two separate yet linked factors; or (4) two separate domains along with an underlying 'common mental distress' (CMD) factor. We defined where, along any latent continuum, the psychopathological items contributed most information. Method: We performed a secondary analysis of cross-sectional, item-level information from measures of depression, anxiety and psychotic experiences in 6617 participants aged 13 years from the Avon Longitudinal Study of Parents and Children (ALSPAC) birth cohort and 977 participants aged 18 years from the ROOTS schools-based sample. We replicated results from one sample in the other and validated the latent factors against an earlier parental measure of mental state. Results: In both cohorts depression, anxiety and psychotic items were best represented as a bi-factor model with a single, unitary CMD factor on which psychotic items conveyed information about the more severe end (model 4); residual variation remained for psychotic items. The CMD factor was significantly associated with the prior parental measure. Conclusions: Psychotic phenomena co-occur with depression and anxiety in teenagers and may be a marker of severity in a single, unitary dimension of CMD. Psychotic phenomena should be routinely included in epidemiological assessments of psychiatric morbidity, otherwise the most severe symptomatology remains unmeasured.